Leadership and Management in Multigenerational Teaching Staff in the New Normal: A Phenomenological Study - Crisanta-Gutierrez Atienza (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
This study looked into the different lived experiences of school principals in the Basic Education Department in Laguna and how they led a multigenerational teaching staff in the new normal. Concerns have also been raised about school leaders' firsthand experiences managing multigenerational teaching staff in the new normal, as well as how they deal with the issues they face. School leaders will be enlightened to provide a roadmap to promote acceptance and flexibility in the abrupt changes from the traditional face-to-face school setting to blended and online delivery of teaching as a result of their shared experiences. The researcher utilized the hermeneutic qualitative research design. The participants of the study were the twelve (12) school principals including the researcher herself who narrated that leading a multigenerational teaching staff creates new challenges for principals. Participants' testimonies can assist leaders in capitalizing on generational differences and using them to foster a positive work environment. Therefore, it became more important for school leaders to have an understanding of order to determine what motivates each generation to contribute effectively to the school in the new normal, researchers looked at each generational group and their differences. Emerging themes from the study include Together as One, Heart to Heart Talk, Work from Home, Better Together, Leading the New Way, Silver Lining, The Generational Divide, An Uphill Climb, A Leader, A Fighter, Peaks and Valleys, e-Support, Leadership that Works and A Competitive Advantage. A compendium of best practices of leadership in multigenerational teaching staff in the new normal was provided in the study. Keywords: hermeneutic, leadership, multigenerational, new normal, phenomenological